An improved model for estimating the TOC in shale formations. (May 2017) - Zhao, Peiqiang; Ma, Huolin; Rasouli, Vamegh; Liu, Wenhui; Cai, Jianchao; Huang, Zhenhua
Abstract: Determination of the total organic carbon (TOC) from well logs is an important step in formation evaluation of shale reservoirs. The ΔlogR model is one of the most commonly used methods in determining the TOC of the source rocks. Wang et al. (2016) made three revisions on ΔlogR model to enhance the prediction accuracy, one of which is to use a changeable slope of log10 Rt versus porosity logs to replace a fixed value. Based on the original ΔlogR model and Wang's revision, we propose an improved model for a better TOC estimation in this paper. Specifically, the approximate linear baseline is replaced by a theoretical one. Under this condition, both the slope and resistivity and porosity log values of the baselined rocks vary from depth to depth. The determination of theoretical baseline is presented, and the varied baseline log values are obtained by a simple mathematical technique. In addition to the shale play of Western Canada Sedimentary Basin, two study areas of Sichuan Basin and Ordos Basin in China, were used to assess the applications of the proposed model and its improvement over the original model. The analysis and discussions presented in this paper indicate that the improved model offers more reliable results in shale plays with large lithological variations. Also, the TOC content of the three study areas was estimated using the proposed model. The results showed that the TOC values estimated from well logs and core analysis are in good agreement. Highlights: An improved model was proposed to estimate the TOC contents. The approximate linear baseline is replaced by a theoretical one. The improved model offers more reliable results in shale plays with large lithological variations. We apply it to the shale plays in Sichuan Basin and Ordos Basin, China.